2023
DOI: 10.1111/ped.15527
|View full text |Cite
|
Sign up to set email alerts
|

Survey of enteral feeding of preterm infants and the human milk bank in Japan

Abstract: BackgroundIn Japan, the first human milk bank (HMB) was established in 2017, which changed the practice of enteral feeding in neonatal care. This study investigated the practice of enteral feeding of preterm infants after the establishment of the HMB in Japan and examined related future issues.MethodsA survey on enteral feeding and the use of the HMB was conducted in 251 neonatal intensive care units (NICUs) from December 2020 to February 2021.ResultsThe response rate was 61%. The ideal times to start enteral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In this current study, the NICUs that had access to HMB replied that the ideal starting time for EN for ELBW infants was within 12 (58.3%) and 24 h (41.7%) after birth. The percentage of NICUs that start EN within 24 h was 30% in all NICUs 8 on the 2020 study and 50% in this study. In other words, NICUs that have access to HMB not only plan to start EN but also start EN as they desire.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…In this current study, the NICUs that had access to HMB replied that the ideal starting time for EN for ELBW infants was within 12 (58.3%) and 24 h (41.7%) after birth. The percentage of NICUs that start EN within 24 h was 30% in all NICUs 8 on the 2020 study and 50% in this study. In other words, NICUs that have access to HMB not only plan to start EN but also start EN as they desire.…”
Section: Discussionmentioning
confidence: 49%
“…In 2020, we conducted a questionnaire survey of all the NICUs that are members of the Japanese Neonatologist Association. The results showed that the ideal starting time for EN for ELBW infants was within 12 and 24 h after the birth of 18% and 58% NICUs, respectively 8 . In this current study, the NICUs that had access to HMB replied that the ideal starting time for EN for ELBW infants was within 12 (58.3%) and 24 h (41.7%) after birth.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations